2018
DOI: 10.1111/jopy.12397
|View full text |Cite
|
Sign up to set email alerts
|

Associations between loneliness and personality are mostly driven by a genetic association with Neuroticism

Abstract: We show that the relationship between loneliness and personality is largely explained by its relationship with Neuroticism, which is substantially genetic in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 73 publications
8
92
3
4
Order By: Relevance
“…61 We showed in another molecular genetic study that loneliness and neuroticism also have a considerable shared genetic etiology with an estimated genetic correlation between .7 and .8. 23 When analyzing the polygenic scores separately, we see a strong negative association with the polygenic score for subjective well-being which, despite relatively low power, suggests a genetic correlation with subjective wellbeing in the same range (or higher) as the genetic correlation with neuroticism and depression. This genetic correlation is likely due to genes that subjective well-being shares with neuroticism and/or depression, which have genetic correlations with well-being of approximately −.8.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…61 We showed in another molecular genetic study that loneliness and neuroticism also have a considerable shared genetic etiology with an estimated genetic correlation between .7 and .8. 23 When analyzing the polygenic scores separately, we see a strong negative association with the polygenic score for subjective well-being which, despite relatively low power, suggests a genetic correlation with subjective wellbeing in the same range (or higher) as the genetic correlation with neuroticism and depression. This genetic correlation is likely due to genes that subjective well-being shares with neuroticism and/or depression, which have genetic correlations with well-being of approximately −.8.…”
Section: Discussionmentioning
confidence: 74%
“…GCTA-GREML and LD score regression have shown that the aggregate of all measured SNPs explain about 14% of the individual differences in loneliness. 23,24 The predictive value of polygenic scores based on individual level DNA data have potential clinical utility beyond that of methods that only estimate SNP-based heritability (eg, GCTA-GREML 25 and LD score regression 21 ), that is why it is important to test their predictive value as we do in our study. Powerful polygenic scores can potentially be used in the clinic as estimates of genetic risk, and have additional applications in a research context, such as the study of interactions between genetic risk and environmental exposures.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Abdellaoui et al, 2019), neuroticism was not the only personality trait that was significantly related to loneliness when controlling for the other four personality traits in this meta-analysis. Consistent with our preregistered hypotheses, extraversion, agreeableness, conscientiousness, and openness were negatively related to loneliness, and neuroticism was positively related to loneliness.…”
Section: Discussionmentioning
confidence: 51%
“…Neuroticism does not predict number of friendships during the freshman year (Selfhout et al, 2010), but it does predict increases in self-reported loneliness (and vice versa; Abdellaoui et al, 2019) and negative life events (Lüdtke, Roberts, Trautwein, & Nagy, 2011;Magnus, Diener, Fujita, & Pavot, 1993). Neuroticism is also associated with the type of behaviours, such as strong reactions to cues of social inclusion (Denissen & Penke, 2008) and inter-moment mood spillovers and general susceptibility to stress (Suls & Martin, 2005), that could explain why neuroticism would predict decreased peer regard, as our results suggest it does.…”
Section: Timing Matters For Personality Effectsmentioning
confidence: 56%